2021
DOI: 10.3390/ijms22168378
|View full text |Cite
|
Sign up to set email alerts
|

High Concentration of an ISS-N1-Targeting Antisense Oligonucleotide Causes Massive Perturbation of the Transcriptome

Abstract: Intronic splicing silencer N1 (ISS-N1) located within Survival Motor Neuron 2 (SMN2) intron 7 is the target of a therapeutic antisense oligonucleotide (ASO), nusinersen (Spinraza), which is currently being used for the treatment of spinal muscular atrophy (SMA), a leading genetic disease associated with infant mortality. The discovery of ISS-N1 as a promising therapeutic target was enabled in part by Anti-N1, a 20-mer ASO that restored SMN2 exon 7 inclusion by annealing to ISS-N1. Here, we analyzed the transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 141 publications
1
17
0
Order By: Relevance
“…Nevertheless, it has been possible to alter sequences to negate the undesirable effects of gapmers by limiting the number of phosphorothioate modified bases to include some bases on a phosphodiester backbone ( Shen et al, 2018 ; Shen et al, 2019 ). Ottesen et al (2021) reported massive perturbation of the transcriptome in SMA patient cells treated with 100 nM of phosphorothioate modified AO targeting SMN2 ISS-N1 , that also triggered widespread aberrant splicing and altered expression of genes involved in transcription, splicing, translation, cell signaling, cell cycle, macromolecular trafficking, cytoskeletal dynamics, and innate immunity. The off-target effects were mitigated to some extent by using shorter ISS-N1 -targeting AOs ( Ottesen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has been possible to alter sequences to negate the undesirable effects of gapmers by limiting the number of phosphorothioate modified bases to include some bases on a phosphodiester backbone ( Shen et al, 2018 ; Shen et al, 2019 ). Ottesen et al (2021) reported massive perturbation of the transcriptome in SMA patient cells treated with 100 nM of phosphorothioate modified AO targeting SMN2 ISS-N1 , that also triggered widespread aberrant splicing and altered expression of genes involved in transcription, splicing, translation, cell signaling, cell cycle, macromolecular trafficking, cytoskeletal dynamics, and innate immunity. The off-target effects were mitigated to some extent by using shorter ISS-N1 -targeting AOs ( Ottesen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, profiling the effects of the ASO candidate on the transcriptome using RNA sequencing analysis in relevant cellular contexts will be important to examine whether the candidate induces off-target effects at a therapeutically relevant concentration, as potential for off-target effects on transcript expression has been reported for splice-switching ASOs. 29 , 30 Given the grave prognosis for SPG49 patients, the potential of TECPR2 exon 8-skipping ASOs to restore TECPR2 expression and function, and the relatively safe profile of this drug class, we expect that this therapeutic approach could ultimately provide clinical benefit to SPG49 patients suffering from TECPR2 exon 8 mutation-induced disease.…”
Section: Discussionmentioning
confidence: 99%
“…For an OND-based approach that targets (pre) mRNA, the use of a human model is essential since there are considerable differences in expressed RNA between mouse and human [ 142 ] as well as in neuronal versus non-neuronal cells. In a study using human fibroblasts and nusinersen, the only FDA- and EMA-approved OND for a CNS disorder, the off-target effects of the splice modulating therapeutic OND nusinersen caused widespread alterations in gene expression (including innate immunity) and aberrant splicing [ 143 ]. However, the interpretation of RNA sequencing studies after OND delivery in cell and animal models is still challenging, distinguishing between off- and on-target effects as well as acute and long-term effects.…”
Section: Toxicities Associated With Cns Local Deliverymentioning
confidence: 99%